Complications of mechanical ventilation in children - Tantalean, José (1996)
Mechanical ventilation (MV) can be lifesaving in children with respiratory failure, but complications may arise. We decided to evaluate the frequency of complications at our ICU. All admissions for MV to the Instituto de Salud del Niño were prospectively evaluated during 17 months. Age, diagnosis, nutritional state, endotracheal tube (ET) size, duration of MV, ventilatory settings and complications like endobrochial intubation (EI), ET blockage, atelectasis, barotrauma (BT), infection and postextubation stridor were recorded. Mean age was 37 mo. (<Id-19 y). Mean duration of MV was 5.7 days, months children with complications duration was longer (p<0.05). There were 228 complications in 142 (31,6%) patients. Malnutrition was detected in 97 (21,6%); they had higher mortality rates (p<0.001, chi square, Yates correction). EI was observed in 47 (10,5%) patients; BT in 66 (14,7%); infection in 46 (10,2%); atelectasis in 44 (9,8%); postexubation stridor in 10 (2,2%); and blockage of ET in 4 (0,9%). Eigth patients died as a result of MV complications. In patients less than 1 month, atelectasis and EI were more frequent (p<0.001 and 0.003, respectively). In patients less than 1 month, atelectasis, infection and BT were more common (p<0.001). Pulmonary interstitial emphysema (PIE) was the most common type of barotrauma. Conclusions: 1) Complications were related to duration of MV; 2) Most deaths due to MV are preventable; 3) Neonates and children with focal lung disease have increased risk of complications; 4) PIE is the most common type of BT children.